2020
DOI: 10.1101/2020.05.12.090787
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Interplay of septin amphipathic helices in sensing membrane-curvature and filament bundling

Abstract: The curvature of the membrane defines cell shape. Septins are GTP-binding proteins that assemble into heteromeric complexes and polymerize into filaments at areas of micron-scale membrane curvature. An amphipathic helix (AH) domain within the septin complex is necessary and sufficient for septins to preferentially assemble onto micron-scale curvature. Here we report that the non-essential fungal septin, Shs1, also has an AH domain capable of recognizing membrane curvature. In mutants lacking a fully functional… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 47 publications
(68 reference statements)
1
1
0
Order By: Relevance
“…To ask if AHs are found outside of opisthokonts and therefore can be an ancestral feature of septins, we developed a high-throughput pipeline to identify AH domains in a large number of polypeptide sequences by predicting alpha helices and then calculating their amphipathicity (see Materials & Methods), and applied it to the NTE and C-terminal extension (CTE) of our eukaryotic septin collection. This pipeline precisely identified previously reported AH domains in fungal and animal septins (Cannon et al, 2019;Lobato-Márquez et al, 2021;Woods et al, 2021), such as Cdc12 and Shs1 in S. cerevisiae and Ashbya gossyppii, human SEPT6, Caenorhabditis elegans UNC-61, and Drosophila melanogaster Sep1 (Fig. S5).…”
Section: Amphipathic Helices Are An Ancestral Feature Of Septinssupporting
confidence: 79%
“…To ask if AHs are found outside of opisthokonts and therefore can be an ancestral feature of septins, we developed a high-throughput pipeline to identify AH domains in a large number of polypeptide sequences by predicting alpha helices and then calculating their amphipathicity (see Materials & Methods), and applied it to the NTE and C-terminal extension (CTE) of our eukaryotic septin collection. This pipeline precisely identified previously reported AH domains in fungal and animal septins (Cannon et al, 2019;Lobato-Márquez et al, 2021;Woods et al, 2021), such as Cdc12 and Shs1 in S. cerevisiae and Ashbya gossyppii, human SEPT6, Caenorhabditis elegans UNC-61, and Drosophila melanogaster Sep1 (Fig. S5).…”
Section: Amphipathic Helices Are An Ancestral Feature Of Septinssupporting
confidence: 79%
“…Previous studies found that under certain conditions, recombinant septin filaments can be paired, possibly through coiled-coil interactions between the C-termini of Cdc3 and Cdc12 (Bertin et al, 2008). However, truncating the coiled-coil of Cdc3 or Cdc12 is lethal, precluding our ability to test this hypothesis in extracts (Finnigan et al, 2015; Woods et al, 2020). Alternatively, filament pairing could be mediated through septin regulators.…”
Section: Resultsmentioning
confidence: 99%